2022
DOI: 10.4067/s0718-235x2022000100087
|View full text |Cite
|
Sign up to set email alerts
|

Ecotourism in Peru: Laguna de los Patos as a case study

Abstract: Aviturismo or birdwatching tourism is part of an emerging subsector in the nature tourism industry. Although bird watching is established in Peru, it has been concentrated to a greater extent in conservation areas. However, the Piura region is also home to a great diversity of birds in areas that have not been declared protected, such as the "Laguna de los Patos" wetland located in the district of Querecotillo. The objective of this study is to investigate the potential of birdwatching that can occur in the "L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
1
0
4
Order By: Relevance
“…Además de ello, espacios como los parques y los santuarios nacionales son utilizados para los llamados corredores ecoturísticos [13]. Esto último sucede también con los valles, las lomas y los cerros [17], [18].…”
Section: A Beneficios Del Ecoturismo En El Perúunclassified
See 3 more Smart Citations
“…Además de ello, espacios como los parques y los santuarios nacionales son utilizados para los llamados corredores ecoturísticos [13]. Esto último sucede también con los valles, las lomas y los cerros [17], [18].…”
Section: A Beneficios Del Ecoturismo En El Perúunclassified
“…Adicionalmente, las investigaciones evaluaron el potencial turístico de actividades, como lo es la observación especies como las aves o también llamado aviturismo [17], [18], y actividades relacionadas con el cultivo y agricultura. Lo que se esperaba con estas actividades era fomentar el cuidado de las especies y también la valoración de los cultivos como la papa.…”
Section: A Beneficios Del Ecoturismo En El Perúunclassified
See 2 more Smart Citations
“…To date, 92 species of birds have been reported, including endemic and migratory birds, as well as 7 species of mammals, 8 reptiles, 2 amphibians and fish. In recent studies there are some species that have no longer been found, such as Buteo polyosoma, Mycteria americana, Fregata magnificens, Pandion haliaetus, Porphyrio martinicus and Charadrius semipalmeatus (Seminario-Córdova, Barrutia, & Estrada, 2022). This situation may be due to adverse situations in this region, such as a decrease in water volume, the scarcity of precipitation in the area, in addition to being exposed to a constant degree of anthropogenic alteration such as road construction, burning of a large part of the 'totora' (Typha angustifolia), furtive hunting of ducks and other causes that alter their feeding or resting habits, depending on the case.…”
Section: Wetlands Considered Within the Ramsar Conventionmentioning
confidence: 99%